Análise genética de características de cresciemento e de reprodução em um rebanho da raça Canchim - Mucari, Talita Buttarello (2006)
The objective in this study was to estimate genetic parameters for the traits days to calving (DC), days to first calving (DFC) and gestation length (GL), associated with reproductive performance of females, as well as to evaluate the relationships of DC and DFC with scrotal circumference at 12 months of age (SC12) and body weights at 12 months of age (W12), at calving (WC), at first calving (WFC), at beginning of the breeding season (WBS) and at beginning of the first breeding season (WFBS), and of GL with weight at birth (BW) and W12. Analyses were done using animal models and the derivative free restricted maximum likelihood methodology. Estimates of heritabilities varied from 0.02 to 0.09 for DC, from 0.15 to 0.23 for DFC and from 0.04 to 0.41 for GL, depending on the data set and the model used for each trait. Genetic correlations of DC and DFC with SC12 showed that it is possible to improve these female reproductive traits by selecting for increase in SC12. With respect to W12, selection to increase this trait should not produce significant changes in DC, but may increase DFC. Associations of the other female body weights with DFC and DC indicated that heavier females experience lower reproductive performance. Estimates of genetic correlations of GL with BW and W12 indicated that selection to change GL will result in correlated response in BW with no changes in W12.